PROSEDUR PEMERIKSAAN MAGNETIC RESONANCE SPECTROSCOPY (MRS) CEREBRAL PADA KASUS GLIOBLASTOMA - Muhammad Syafi’ie; Imtiyaz Putri Hafizhah (JRI (Jurnal Radiografer Indonesia), 2021)
ABSTRACT Background: Magnetic Resonance Imaging (MRS) can be applied to characterize existing musculoskeletal disorders to help determine the next medical examination. According to Florez-Alvarez et al. (2020), MRS examination in glioblastoma cases was carried out with multi voxel technique using 144 ms TE to optimally evaluate Choline (Cho) and N-acetyl asparate (NAA). Meanwhile, MRS examination in glioblastoma cases at the Radiology Department of RSUP DR. Sardjito was performed with multi voxel method using a TE of 40 ms. Methods: This research was conduted at the Radiology Department of RSUP DR. Sardjito Yogyakarta used a Siemens Sykra 3T in April 2021 for a patient with a diagnosis of glioblastoma who had complaints of dizziness and weakness of the right side of the body. This cerebral MRS examination using multi voxel method using a TE of 40 ms. Results: Based on the results of cerebral MRS examination in cases of glioblastoma at the Radiology Department of RSUP DR. Sardjito Yogyakarta, obtained the spectrum of Cho (11.0) NAA (0.00) in the tumor area, Cho (3.89) NAA (3.23) in the panumbra area, and Cho (5.91) NAA (12.7) in the healthy tissue area that can indicate a cell damage and can be graded with more complex calculation. Conclusions: The MRS examination was carried out using a 40 ms TE with multi voxel localixzer technique could more optimally evaluate the spectrum of Cho and NAA metabolites, where the two metabolites became the main reference in determining tumor pathology, especially glioblastoma when compare to 144 ms TE.